METHOD OF MANAGEMENT SOFTWARE PRODUCTS USABILITY - Гурченко, І. (Science-based technologies, 2012)
In this paper the ontology of software usability is constructed by analyzing the subject area. Within the ontology the concept of usability as a software quality characteristic, aspects of usability research, concepts and tasks of usability management are defined. The methods and means of assurance of user-specified usability level are analyzed. An issue of usability achieving and maintaining using well-known process approach to quality management is examined. The paper presents the solution of the problem of software usability management according to the developed method.